2014
DOI: 10.1016/j.jdent.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vehicles to collect dentinal fluid for molecular analysis

Abstract: OBJECTIVES To test the hypothesis that a material with higher water absorption than polyvinylidene fluoride (PVDF) could increase the yield of target molecules from exposed dentine. METH-ODS In a series of standard tests, different cellulose membranes were compared to a PVDF counterpart for their ability to absorb water and release protein. In a subsequent randomized clinical trial, the cellulose material with the most favourable values was compared to PVDF regarding the levels of MMP-2 that could be collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
(32 reference statements)
0
13
0
1
Order By: Relevance
“…Dentin fluid is the extracellular fluid that is contained within dentinal tubules [109]; its composition includes inflammatory mediators and vasoactive compounds associated with inflammation. While initial evidence suggested that these mediators can be assayed [33] problems exist with protein yield [27] and the need to remove the existing restoration or in other cases to prepare an initial cavity deep in dentin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentin fluid is the extracellular fluid that is contained within dentinal tubules [109]; its composition includes inflammatory mediators and vasoactive compounds associated with inflammation. While initial evidence suggested that these mediators can be assayed [33] problems exist with protein yield [27] and the need to remove the existing restoration or in other cases to prepare an initial cavity deep in dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggests that the dental pulp is not an isolated entity in an encased, solid environment but a reactive tissue that extends its biological products into the outside environment [24, 25]. In fact, studies have shown that pulpal events can be reflected through measurable levels of protein markers that correlated with pulpal symptoms in pulpal blood [26], dentinal fluid [27], periapical fluid [28], and gingival crevicular fluid (GCF; [1, 29]).…”
Section: Introductionmentioning
confidence: 99%
“…Die Pulpa gilt als ein reaktives Gewebe, das mit dem umliegenden Gewebe interagiert. Änderungen von Proteinmarkern im Pulpablut [49], im Dentinliquor [50], im apikalen Fluid [51] und in der Sulcusflüssigkeit [52], die mit pulpitischen Symptomen korrelierten, wurden bereits nachgewiesen. Bis jetzt hat die molekulare Diagnostik allerdings bei endodontischen Fragestellungen im Hinblick auf Diagnostik und Therapieplanung noch keinen Einzug in den klinischen Alltag gehalten [53].…”
Section: Abwehrmechanismen Der Pulpaunclassified
“…It would be most interesting to evaluate whether such assays could also be developed for the analysis of dentinal and periapical fluid. With the former, there will most likely be a sensitivity problem as the target proteins collected from dentinal fluid are in the low ng range . However, with periapical fluid, yields are similar to GCF and assays could easily be developed.…”
Section: Chairside Assays: Will They Ever Be Possible?mentioning
confidence: 99%